'The Opportunity Exists. Why Don't They Seize It?' Political (In)Competence and the Potential of ICTs for Good Governance in Niger Republic. Issue 1 (12th May 2015) - Alzouma, Gado
An increasing number of scholars, political activists, humanitarian workers, and peacebuilding strategists are now advocating ICTs for fostering democratic participation and good governance in Africa. For their part, governments are devising policies geared towards helping citizens controlling their own destiny through the use of ICTs. They are backed by international development organizations that are implementing numerous programmes and projects centered on the notions of e-government, e-governance, and e-democracy. All those concerned actors and development workers are particularly encouraged by the fact that digital devices are becoming increasingly available for public use on the continent. However, so far, we lack clear evidence that African citizens are actually using, in their everyday lives, digital tools for governance, political participation, and peacebuilding purposes. Based on the case of Niger Republic, this study seeks to contribute to answering this question through semi-structured interviews carried out with Nigerien social media users. It shows that many factors including illiteracy, and particularly digital illiteracy, lack of political will, inefficient methods and poor understanding of social media potential contribute to strongly mitigate digital activities when it comes to access, governance, political participation and peacebuilding.